Technical note : quantifying size and shape of entheses - Henderson, C. Y. (2012)
Entheseal changes (ECs) have been widely recorded using visual methods, but size and shape affect stress distribution which cannot be quantified visually. The aim of this paper is to present a simple method for quantifying size and shape by applying parameters to quantify shape and to highlight preliminary results indicating that this method provides useful data. Hypotheses tested were: common extensor origin size correlates with humerus size; ECs change the size and shape of entheses; surface area is increased in those entheses with bony proliferation. The common extensor origins of 43 male skeletons from medieval York were recorded. The entheses were recorded visually for any deviation from a smooth surface. The chord was measured using sliding calipers and the shape of the entheses recorded using a profile gauge and quantified using parameters (e.g. the standard deviation of the surface from a mean line) which assess the relationship of the surface to a flat surface. To test replicability, disarticulated humeri were also recorded (inter-observer error n = 9; intra-observer error n = 20) using the same methodology. Replicability for size and shape was good for intra-observer error but weaker for inter-observer error. There is variability in enthesis size and distal humeral condyle size; normal entheses are smaller than those with EC while their surface shape differs and is affected by the type of EC (proliferative or destructive); surface area in those entheses with proliferative ECs is increased. The use of these parameters for quantifying enthesis size and shape provides insights into enthesis variability which cannot be tested using visual methods alone. These parameters can be recorded using this two-dimensional method or can be measured on data collected with a laser scanner. Future research will test the relationship between surface size/shape and the effects of biological sex, age and occupation.